Magia e poder no Egito tardio: a emergência dos sacerdotes magos como 'theioi andres' (séc. III ao V d.C.) - Bocayuva, Hariadne da Penha Soares (2020)
This thesis aims to analyze the formation and emergence of Egyptian magicians-priests as theioi andres, divine men, and their role as power agents in late Egypt between centuries III and V A.D. As theioi andres the magicians-priests acquired comprehensive